Airpower pioneers from Billy Mitchell to Dave Deptula - Olsen, John Andreas 1968- (Naval Institute Press, 2023)
"Airpower Pioneers studies twelve especially influential airmen, detailing their impact on the evolution of the United States Air Force (USAF). This book describes the personal qualities and careers of people who distinguished themselves first and foremost by advancing airpower theory, doctrine, and strategy, and in certain cases by implementing significant organizational changes in the USAF structure."
Keywords: United States / Air Force / Biography; Generals / United States / Biography; Air power / United States / History; Aeronautics, Military / United States / History; HISTORY / Military / Aviation & Space; HISTORY / Military / United States; United States / Air Force; Aeronautics, Military; Air power; Generals; United States; Biographies; History